KOREAN LANGUAGE STYLES - Azimova Amira Muminovna; Olimjonova Asalabonu Ziyodjonovna (American Journals, 2023)
The Republic of Korea is one of the countries in East Asia in which Confucianism is regarded as a system of moral and ethical values that regulate the relationship of people and encourage them to be followers of the highest wisdom that determines the norms of justice, righteousness and conformity of man, whatever place he occupies in the socio-social hierarchy.
Keywords: Culture, Confucian ethics, structures, degree of politeness and style of writing, familiar or friendly style, conversation, dialogue.